The Digital Television Revolution - Starks, M. author. aut Link
XVII, 264 p.
Keywords: This account of the global switch to digital television, from its origins to its emerging outcomes, provides an understanding of how digital television is converging with the Internet. It pictures a future in which the democratic role of the media, freedom of expression and democratic participation can be enhanced.